The Impact of Board Independence, Institutional Ownership, and Audit Committees on Corporate Tax Aggressiveness - Sari, Ni Made Citra Riani; Sudana, I Putu (E-Jurnal Akuntansi; Vol 35 No 5 (2025)DO - 10.24843/EJA.2025.v35.i05.p04, 2025)
This study examines the impact of audit committees, institutional ownership, and independent boards of commissioners on tax aggressiveness. The sample consists of 44 banking institutions listed on the IDX between 2018 and 2022, yielding 128 research observations. Purposive sampling was employed to select the sample, and multiple linear regression analysis was used to analyze the data. The findings suggest that the presence of an independent board of commissioners significantly reduces tax aggressiveness, indicating a positive correlation between a higher proportion of independent commissioners and lower levels of tax avoidance. However, no significant relationship was found between institutional ownership, audit committees, and tax aggressiveness, suggesting these variables may not influence corporate tax strategies in the same way. Keywords: Independent Board of Commissioners; Institutional Ownership; Audit Committee; Tax Aggressiveness